Great Barrier Reef Expedition 1928-1929 scientific reports. (London, U.K. British Museum Natural History, 1932)
Contents: v. 6 no. 6 Foraminifera by A. C. Collins; v. 4 no. 15 The silicoflagellata and tintinnoinea by Shiena M. Marshall; v. 4 no. 14 Sponges by Maurice Burton; ; v. 4 no. 3 Nemertea by J. F. G. Wheeler v. 4 no. 12 The Polyzoa with a note on an associated hydroid by Anna Hastings and v.5 no.8 Chaetognatha by S. T. Burfield
Keywords: Great Barrier Reef; Marine invertebrates